Anisotropic assembly and fluorescence enhancement of conjugated polymer nanostructures. Issue 6 (7th September 2022) - Men, Xiaoju; Fang, Xiaofeng; Liu, Zhihe; Zhang, Zhe; Wu, Changfeng; Chen, Haobin
Abstract: The electronic properties of conjugated polymers depend sensitively on their conformation and morphology. However, control over the morphology of conjugated polymers is highly challenging. Here, we demonstrate a facile approach for assembling conjugated polymers into anisotropic nanostructures. In a water–tetrahydrofuran (H2 O–THF) binary solvent, we prepared ellipsoidal nanoparticles, which can subsequently self‐assemble into triangle‐ring and rod‐like nanostructures in a stepwise manner. The transitions among these morphologies can be rationally regulated by tuning the volume ratio of H2 O to THF and the polymer concentration. The nanostructures show shape‐dependent absorption from 383 to 403 nm and significant fluorescence enhancement with a quantum yield up to 70%. The oxetane groups in the polymer side chains and the presence of surfactant in the solvent are decisive for the anisotropic assembly. We further demonstrate multicolor fluorescent nanowires with good structural integrity over doping of dye molecules or other fluorescent polymers. Single nanowires were characterized by high‐order super‐resolution optical fluctuation imaging, which revealed spatial distribution of the photooxidation sites along single nanowire for easily generating hole polarons. Graphical Abstract: A facile, one‐step self‐assembly is achieved for forming conjugated polymers into anisotropic nanostructures such as ellipsoids, triangle‐rings, and nanowires. The nanostructures exhibit shape‐dependent absorption and fluorescence enhancement. Single nanowires were characterized by high‐order super‐resolution optical fluctuation imaging, which revealed spatial distribution of the photooxidation sites along single nanowire for easily generating hole polarons.